A Photogrammetric Method for Spatial Data Extraction from Google Earth and Improvement with Precision Analysis - Karimi, Sadegh; Khorrambakht, Ehsan (Civil Engineering Journal, 2018)
Topography maps are crucial for civil engineering projects, such as road construction, water channel construction, urban construction, and mining. Here we present a method which enables us to extract topographical map via modeling Google Earth and some field works. In this method, first, we model Google Earth as an object with closed-range photogrammetric method in the Agisoft Photoscan. Through some field works, we measured twenty-two points including twelve ground control points (GCP) and ten independent check points (ICP). Due to these GCPs, we were able to transform our model to real world with global polynomial and multi-quadratic equations and ICPs were used for precision analysis. This method is easy and cheap to obtain spatial data and the accuracy is sufficient for research requirements.